THE EFFECTIVENESS OF TEACHING SOME MODERN METHODS IN LEARNING BASIC SKILLS IN VOLLEYBALL AND ITS IMPACT ON REDUCING STANDING AWKWARDNESS AMONG STUDENTS OF PREPARATORY SPORTS TEAMS - Waleed Mohamed Ali Hussain Al-Shahwani (Proximus Journal Publishing, 2025)
The Effectiveness of Teaching the Method of Self-Examination in Learning Some Basic Skills of Volleyball among Students of Sports Teams for the Preparatory Stage The difference between the self-examination method and the command method in learning some basic volleyball skills among the students of the sports teams of the preparatory stage.
Keywords: students; Preparatory; teams